2005
DOI: 10.1242/jeb.01796
|View full text |Cite
|
Sign up to set email alerts
|

Prior classical olfactory conditioning improves odour-cued flight orientation of honey bees in a wind tunnel

Abstract: Odours are key cues used by the honey bee in various situations. They play an important role in sexual attraction, social behaviour and location of profitable food sources. Here, we were interested in the role of odours in orientation at short distance, for instance the approach flight to a floral patch or in close proximity to the hive entrance. Using a newly designed wind tunnel, we investigated the orientation behaviour of the bee towards two different odours: a social odour and a floral component, linalool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Thus, retention tests should be performed in an operant context, where insects can freely behave in response to the learned stimulus. Previous studies in fruit flies (Tully and Quinn, 1985), honeybees (Sandoz et al, 2000;Chaffiol et al, 2005) and crickets (Matsumoto and Mizunami, 2002a) have shown that insect olfactory memories are resistant to such context changes. In the cricket, classical olfactory conditioning evoked a subsequent change in olfactory preference in an open test arena that lasted from 2h to 4days (Matsumoto and Mizunami, 2002a;Matsumoto and Mizunami, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, retention tests should be performed in an operant context, where insects can freely behave in response to the learned stimulus. Previous studies in fruit flies (Tully and Quinn, 1985), honeybees (Sandoz et al, 2000;Chaffiol et al, 2005) and crickets (Matsumoto and Mizunami, 2002a) have shown that insect olfactory memories are resistant to such context changes. In the cricket, classical olfactory conditioning evoked a subsequent change in olfactory preference in an open test arena that lasted from 2h to 4days (Matsumoto and Mizunami, 2002a;Matsumoto and Mizunami, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…The use of freely moving animals is therefore necessary to evaluate the associations established during conditioning. In the case of PER conditioning, the positive (attractive) quality acquired by the odour after pairing with sucrose was clearly shown by experiments in which bees previously conditioned in a PER protocol demonstrated an increased orientation towards the odour, either when walking in a four-armed olfactometer (Sandoz et al, 2000) or when flying in a wind tunnel (Chaffiol et al, 2005). These and other experiments in bees (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Gerber et al, 1996;Sandoz et al, 2000;Chaffiol et al, 2005;Mc Cabe and Farina, 2009). However, none of these previous studies provided the precise control of experience and/or the bi-directional transfer in both contexts achieved in our work.…”
Section: Information Transfer Between Different Experimental Contextsmentioning
confidence: 99%